2019
DOI: 10.1002/jcb.29148
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Downregulation of miR‐218 by nicotine promotes cell proliferation through targeting CDK6 in non–small cell lung cancer

Abstract: Background Nicotine, an important component of tobacco, is a major risk factor of lung cancer, but the mechanism through which nicotine promotes lung cancer development remains unclear. Methods Eighty patients with lung cancer were enrolled in this study, 34 of whom did not smoke and the others did. The expression of miR‐218 and CDK6 messenger RNA (mRNA) was measured using quantitative reverse transcription polymerase chain reaction (qRT‐PCR). A luciferase reporter system was used to identify the direct target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…42 Similarly, the nicotine-induced proliferative effects were rescued by the recovery of the expression levels of CDK6 in NSCLC. 43 These findings also indicated that CDK6 might also have an oncogenic role in NSCLC, which is consistent with our results that the expression of CDK6 was increased in lung cancer tissues than in the paired adjacent normal tissues, especially in the LUSC, and that higher expression of CDK6 was associated with a worse survival of patients with NSCLC. Furthermore, the CDK6 rs113181986 C allele was correlated with decreased mRNA expression of CDK6 and a better outcome in patients with NSCLC, which supports the biological plausibility of the findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…42 Similarly, the nicotine-induced proliferative effects were rescued by the recovery of the expression levels of CDK6 in NSCLC. 43 These findings also indicated that CDK6 might also have an oncogenic role in NSCLC, which is consistent with our results that the expression of CDK6 was increased in lung cancer tissues than in the paired adjacent normal tissues, especially in the LUSC, and that higher expression of CDK6 was associated with a worse survival of patients with NSCLC. Furthermore, the CDK6 rs113181986 C allele was correlated with decreased mRNA expression of CDK6 and a better outcome in patients with NSCLC, which supports the biological plausibility of the findings.…”
Section: Discussionsupporting
confidence: 91%
“…It was previously reported that LncRNA associated with poor prognosis of hepatocellular carcinoma could accelerate the progression of NSCLC by upregulating CDK6 42 . Similarly, the nicotine‐induced proliferative effects were rescued by the recovery of the expression levels of CDK6 in NSCLC 43 . These findings also indicated that CDK6 might also have an oncogenic role in NSCLC, which is consistent with our results that the expression of CDK6 was increased in lung cancer tissues than in the paired adjacent normal tissues, especially in the LUSC, and that higher expression of CDK6 was associated with a worse survival of patients with NSCLC.…”
Section: Discussionsupporting
confidence: 90%
“…mir, microrna; nSclc, non-small cell lung cancer; PTen, antiphosphatase and tensin homolog; BMi-1, anti-polycomb complex protein BMi-1; YY1, anti-transcriptional repressor protein YY1; VeGF, vascular endothelial growth factor. which was consistent with other studies (32,34,41). The effect of mir-218 on cell cycle progression was further investigated using flow cytometry.…”
Section: Discussionsupporting
confidence: 90%
“…as a tumor-suppressor mirna, mirna (mir)-218 is downregulated in tumor progression and is associated with prognosis in nSclc (30)(31)(32). Furthermore, mir-218 can participate in tumor progression by regulating target genes including PXN, IL6R, JAK3, SLUG, ZEB2, EGFR, MEF2D, CDCP1, RUNX2, HMGB1, ETK, HOXA1, CDK6 and ROBO1 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The present study revealed for the first time, to the best of the authors' knowledge, the expression levels and therapeutic potential of mir-218 in XWlc-05.…”
Section: Introductionmentioning
confidence: 99%
“…After subsequently culturing the cells in a complete culture medium for 24‐48 hours, the cells were collected, and their RNA and protein were extracted for analysis. The primer sequence for miR‐218 mimic was: 5′UUGUGCU UGAUCUAACCAUGU3′, 21 and that for miR‐218 inhibitor was: 5′AACACGA ACUAGAUUGGUACA3′.…”
Section: Methodsmentioning
confidence: 99%